The language issue in the teaching of mathematics in South Africa : intermediate phase research from one province - Tshuma, Lindiwe (SunPress, 2020)
"The book is the result of a five-year project that culminated (within the first three years) in doctoral research interrogating language competency for meaningful mathematics instruction at upper primary level conducted at University of Stellenbosch in 2017; and this book in the succeeding two years. The initial research project received countrywide coverage in several South African media outlets including Times Live and Radio 2000"--Publisher's description